2000
DOI: 10.1095/biolreprod63.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sperm Sulfogalactosylglycerolipid in Mouse Sperm-Zona Pellucida Binding1

Abstract: Sulfogalactosylglycerolipid (SGG) is the major sulfoglycolipid of mammalian male germ cells. Like other sulfoglycolipids, SGG is believed to be involved in cell-cell/extracellular matrix adhesion. Specifically, we investigated whether sperm SGG played a role in sperm-egg interaction. Initially, we produced an affinity-purified, rabbit polyclonal immunoglobulin (Ig) G antibody that specifically recognized SGG (anti-SGG). Indirect immunofluorescence using anti-SGG IgG localized SGG to the convex and concave ridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 53 publications
1
62
0
Order By: Relevance
“…This is possible, since prosaposin is present in the oviductal fluid (M Schenk, DC Santos and N Tanphaichitr, unpublished observations) and cathepsin D, which is known for its processing activity of prosaposin to saposin B (Hiraiwa et al 1997), is also released as part of the AC (Erickson & Martin 1974). This SGG desulfation may be essential; acrosomal vesicles would still adhere to the ZP due to SGG affinity for the ZP (White et al 2000), thus impeding sperm migration through the ZP layer. On the other hand, galactosylglycerolipid (GG), the desulfated product of SGG, has minimal affinity for the ZP (White et al 2000) and would thus be released into the surrounding.…”
Section: Wtmentioning
confidence: 99%
See 1 more Smart Citation
“…This is possible, since prosaposin is present in the oviductal fluid (M Schenk, DC Santos and N Tanphaichitr, unpublished observations) and cathepsin D, which is known for its processing activity of prosaposin to saposin B (Hiraiwa et al 1997), is also released as part of the AC (Erickson & Martin 1974). This SGG desulfation may be essential; acrosomal vesicles would still adhere to the ZP due to SGG affinity for the ZP (White et al 2000), thus impeding sperm migration through the ZP layer. On the other hand, galactosylglycerolipid (GG), the desulfated product of SGG, has minimal affinity for the ZP (White et al 2000) and would thus be released into the surrounding.…”
Section: Wtmentioning
confidence: 99%
“…This SGG desulfation may be essential; acrosomal vesicles would still adhere to the ZP due to SGG affinity for the ZP (White et al 2000), thus impeding sperm migration through the ZP layer. On the other hand, galactosylglycerolipid (GG), the desulfated product of SGG, has minimal affinity for the ZP (White et al 2000) and would thus be released into the surrounding. We are currently investigating these possibilities to gain a better understanding of ASA-ZP interaction.…”
Section: Wtmentioning
confidence: 99%
“…In addition, in sea urchin, sperm gangliosides have been shown to bind to sperm-binding proteins localized on the vitelline layer of the egg surface 34 . Furthermore, in mice, sperm sulfogalactosylglycerolipids have been shown to bind to the egg extracellular sulfoglycoprotein matrix, the zona pellucida 35 . These data suggest that sperm glycolipids are involved in fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, a raft lipid component, SGG, is a ZP adhesion molecule (23,41). Proteomic analyses reveal that a number of proteins known for their affinity for or association with the ZP are also present in isolated sperm lipid rafts, including PH-20 (46,47), basigin (46), spermadhesins (48), proacrosin (48), TESP1 (46), TESP5 sn (49) and N-acetylglucosamine:beta-1,4-galactosyltranferase (47).…”
Section: E Lipid Rafts In Capacitated Sperm As Platforms For Egg Intmentioning
confidence: 99%
“…Besides these biochemical characterizations, we have shown that the functional properties of isolated sperm rafts are partially dependent on SGG. We have demonstrated that detergent resistant lipid rafts of capacitated pig sperm have the ability to bind to the egg zona pellucida glycoproteins (ZP), and this binding ability is partially attributed to SGG affinity for the ZP (23,41). SGG is also present in plasma membrane vesicles of the sperm head anterior, isolated from live sperm by nitrogen cavitation.…”
Section: Cmarkers For Sperm Lipid Raftsmentioning
confidence: 99%